Blunt thoracic trauma: recent advances and outstanding questions. Issue 6 (December 2015) - Parry, Neil G.; Moffat, Bradley; Vogt, Kelly
Abstract : Purpose of review: The treatment of blunt thoracic injuries is complex and evolving. The aim of this review is to focus on what is new with ventilation for blunt chest trauma as well as an update on the current management strategies for blunt aortic injury and rib fractures. Recent findings: Early use of noninvasive ventilation appears to be well tolerated in select hemodynamically stable blunt trauma patients. For those patients requiring intubation, airway pressure release ventilation is an excellent mode to decrease the risk of posttraumatic acute lung injury. Endovascular repair of blunt thoracic aortic injuries provides benefit over open repair and, if possible, delayed repair confers a mortality advantage. Despite its increasing use, there continue to be conflicting results about the role of surgical rib fixation for the treatment of flail chest. Summary: Blunt thoracic injuries are commonly treated in the ICU and a solid knowledge of mechanical ventilation strategies (both noninvasive and invasive) is essential. Blunt thoracic aortic injuries require early diagnosis and aggressive blood pressure management. Not all such injuries need operative repair but those that do benefit from an endovascular approach. The management of flail chest includes early aggressive multimodal analgesia, adequate oxygen, and ventilatory support. Surgical rib fixation should be considered in select patients.